APAKAH MANAJEMEN LINGKUNGAN PERLU DIIMPLEMENTASIKAN DALAM MENCIPTAKAN KINERJA LINGKUNGAN YANG BAIK DAN KINERJA KEUANGAN YANG OPTIMAL? - Vinky Liestoya Putri; Ina Indriana (Tirtayasa Ekonomika, 2017)
The purpose of this study was to determine the effect of environmental management on environmental performance and the effect of environmental performance on financial performance. The study uses panel data, the data used in this study are cross section data and time series data. The company that is used as the unit of analysis in this study is companies that are listed on the Indonesia Stock Exchange (IDX) in 2011-2014. Based on the sampling technique used purposive sampling method, obtained a sample of 96 out of a total of 24 listed companies. While the data analysis technique used in this study is ordinal logistic regression analysis and simple linear regression analysis with the OLS method. Based on the results of testing the hypothesis it can be concluded that environmental management has a significant positive effect on environmental performance, and the same conclusion also applies to testing the effect of environmental performance on the company's financial performance.